Seinfeldia : how a show about nothing changed everything - Armstrong, Jennifer Keishin (Simon & Schuster, 2016)
"An uproarious behind-the-scenes account of the creation of the hit television series describes how comedians Larry David and Jerry Seinfeld dreamed up the idea for an unconventional sitcom over coffee and how, despite network skepticism and minimal plotlines, achieved mainstream success,"--NoveList.